Infiltração policial : perspectiva processual e probatória - Faria, Frederico da Costa Marques (2015)
This study seeks to analyze an investigative tool used in several countries and recently regulated in Brazil. The analysis begins with the description of the phenomenon of organized crime and its change throughout history, as well as the evolution of investigative techniques especially the infiltration of agents. Then we draw the legislative path that finally led to Law 12.850/13, that currently rules this institute. We then proceeded to examine each of the diploma elements to form the basis for the core of the work that are the procedural and evidentiary aspects of the tool. In the last chapter, we analyze the adequacy of the investigative technique to the principles of criminal procedure and those inherent to the police infiltration itself.